Study on Dissimilar Aluminium Alloys of AA7075 and AA6061 using Friction Stir Welding - N. A. A., Sathari; A. R., Razali; M., Ishak; L. H., Shah (2014)
The present study focuses on the effects of material position and tool rotational speed on tensile strength of dissimilar aluminium alloys welded of AA707 1 and AA6061 with thickness of 2.0 mm using conventional milling machine. Ten joints were produced by varying tool rotational speeds and by changing the fixed position of material in advancing and retreating side. The result shows that the rotational speed and material position influenced the tensile strength value of dissimilar welds. The welded joints showed maximum tensile strength of 207 MPa when aluminium alloys of AA606 I were placed in advancing side at 1000 rpm, while minimum tensile strength value of 160 MPa were obtained at 1000 rpm when AA7075 was placed in advancing side except for rotational speed beyond 1200 rpm that shows increasing in tensile strength values.